Parallel Business Processes Modeling - G. N. Kalyanov (Открытое образование (Москва))
The article considers a new section of the modern theory of business processes dedicated to their parallel processing. The relevance of the work is due to the need to reorganize business processes in order to improve a number of their key indicators, such as speed, cost, etc.It should be noted that the well-known models and methods of the modern theory of business processes practically do not address the issues of parallelism in them, although this direction occupies a significant place in the general theory of processes and, in addition to the actual methods of description, analysis and verification of parallel structures, also includes methods of parallelization of sequential structures.The paper proposes a classification of parallel business processes based on the types of parallel computing systems and completely covering the subject area under consideration. Examples of parallel business processes of each type are given. For each of the selected classes of business processes, a brief overview of the current state of affairs in terms of parallelism is given; the directions of relevant work are identified and analyzed. Brief descriptions of models and methods of pipelined and synchronous parallelism are given.In terms of asynchronous parallelism, a model and language tools for organizing parallel independent branches (processes) are proposed. A mixed graph containing nodes and branches of various types is used as the corresponding model. The scenario of executing a parallel business process is formalized. To estimate the execution time of a parallel business process, the basic theorems of the theory of computational processes are adapted in order to focus them on business processes, recommendations are given on the rules for building parallel business processes. The requirements for the language tools for describing asynchronous parallel business processes are formulated.Next, the methods of parallelization of business processes related to its linear sections and cycles are considered. The definitions of the linear section and the cycle in the business process are introduced. For their parallelization, the key task is to identify information dependencies between the functions of the business process. Attention is drawn to the sequence of definitions/uses of information objects, manifested through incoming and outgoing information flows for functional objects of the corresponding visual modeling language. In terms of the above-mentioned business process graph, the concepts of information dependence of various types are formalized.The proposed work is one of the first attempts to build a formal basis for the organization of parallelism in business processes, which plays an important role in improving the key indicators of business processes in the tasks of their reorganization.